Guidance on the assessment of the safety of feed additives for the environment. (5th April 2019) - ,; Bampidis, Vasileios; Bastos, Maria; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: This guidance document is intended to assist the applicant in the preparation and the presentation of an application, as foreseen in Article 7.6 of Regulation (EC) No 1831/2003, for the authorisation of additives used in animal nutrition. It specifically covers the assessment of the safety for the environment. Draft endorsed by the FEEDAP Panel 2 October 2018 Submitted for public consultation 8 October 2018 End of public consultation 19 November 2018 Adoption by the FEEDAP Panel 27 February 2019 Implementation date 1 September 2019 Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2019.EN-1595/full